Titik Temu Konsepsi Keselamatan dalam Islam dan Katolik - Abdullah, Abdullah (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2011)
This article elaborates the concept of salvation based on Islam and Chatolic. It is clearly stated that both religios define salvation as happiness, escaped from the danger, perfect condition, and healthy life. Generally speaking, the main focus of this article is how do Islam and Chatolic describes the epistemology of salvation. The author found that God has already explained the concept of salvation either on Quran or al-Kitab. Both holy books clearly stated that no god except the One. In other words, these religios generated an understanding of the concept of monotheism. At least, as contended by the author, there are two different approaches to see the concept of salvation. Firstly, esoteric approach, this concentrates on how religions can be seen internally as well as substantively. To put simply, religions tend to get same direction, namely one God. Secondly, exoteric approach, religions may be approached through different ways of worship. Religion followers look different on doing worship, but, basically, they go on the same direction.